A Note on the Multi-Commodity Warehouse Problem - Eastman, Willard L. (Management Science, 1959)
The warehouse problem requires the determination of a sequence of buy and sell decisions at discrete points in time. By equating points in time and points in space, the warehouse problem can be identified with a special case of the shortest-route problem. In the present note a special matrix formulation is employed to yield simple solutions to both problems. An example is included to illustrate the method.